2013
DOI: 10.1242/dmm.013235
|View full text |Cite
|
Sign up to set email alerts
|

Impaired embryonic motility indusp27mutants reveals a developmental defect in myofibril structure

Abstract: An essential step in muscle fiber maturation is the assembly of highly ordered myofibrils that are required for contraction. Much remains unknown about the molecular mechanisms governing the formation of the contractile apparatus. We identified an early embryonic motility mutant in zebrafish caused by integration of a transgene into the pseudophosphatase dual specificity phosphatase 27 (dusp27) gene. dusp27 mutants exhibit near complete paralysis at embryonic and larval stages, producing extremely low levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 61 publications
4
24
0
Order By: Relevance
“…In addition, MK-STYX downregulates CUGBP, elav-like family member 2 (CELF2) (Figure 6Bii) [33], which may serve as the rationale for the pro-proliferative and anti-apoptotic functions of MK-STYX in hepatocellular carcinoma. The relationship of STYXL2 (DUSP-27) to diseases is not as well established as that of STYX and MK-STYX; however, STYXL2 may have a potential role in paralysis [59,99]. STYXL2 lacks the critical conserved cysteine reside, which was replaced by serine (Figure 5B,C) [59], and is expressed in skeletal and cardiac muscle [99].…”
Section: Styx Pseudophosphatases In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MK-STYX downregulates CUGBP, elav-like family member 2 (CELF2) (Figure 6Bii) [33], which may serve as the rationale for the pro-proliferative and anti-apoptotic functions of MK-STYX in hepatocellular carcinoma. The relationship of STYXL2 (DUSP-27) to diseases is not as well established as that of STYX and MK-STYX; however, STYXL2 may have a potential role in paralysis [59,99]. STYXL2 lacks the critical conserved cysteine reside, which was replaced by serine (Figure 5B,C) [59], and is expressed in skeletal and cardiac muscle [99].…”
Section: Styx Pseudophosphatases In Diseasementioning
confidence: 99%
“…The relationship of STYXL2 (DUSP-27) to diseases is not as well established as that of STYX and MK-STYX; however, STYXL2 may have a potential role in paralysis [59,99]. STYXL2 lacks the critical conserved cysteine reside, which was replaced by serine (Figure 5B,C) [59], and is expressed in skeletal and cardiac muscle [99]. STYXL2 is a downstream target of the Janus activated kinase/Signal transducers and activators of transcription signaling pathway [99], suggesting that STYXL2 has important roles in signaling cascades.…”
Section: Styx Pseudophosphatases In Diseasementioning
confidence: 99%
“…In order to do this, we generated a Tg(uas:egfp-2a-rpl10a2xHA) y531 UAS:RiboTag transgenic line to drive expression of the RiboTag cassette in any tissue or cell type of interest for which a Gal4 driver line is available (Figure 7A,E). The UAS:RiboTag line showed strong, tissuespecific expression after being crossed to a variety of different Gal4 driver lines, including a muscle-specific Tg(xa210:gal4) y241 line (Figure 7B; (Fero et al, 2014), an endothelialspecific Tg(fli1a:gal4ff) ubs4 line (Figure 7C; (Zygmunt et al, 2011), and a neural-specific Tg(huC:gal4) line (Figure 7D; (Kimura et al, 2008). TRAP isolation of mRNA from embryos obtained from each of these crosses revealed strong enrichment of tissue-specific genes in samples prepared from the appropriate lines (Figure 7E).…”
Section: A Ribotag Reporter Line For Profiling Cells and Tissues Of Imentioning
confidence: 99%
“…Functionally, STYXL2/DUSP27 has been found to be a downstream target of the JAK/STAT signaling cascade, and knockdown of STYXL2/DUSP27 in C 2 C 12 cells inhibited myogenic differentiation (7). Loss of functional STYXL2/DUSP27 was found to cause disorganized myofibril formation and near-paralysis in zebrafish, whereas studies examining the role of STYXL2/DUSP27 in skeletal muscle found it to localize in a banding pattern that may be indicative of sarcomere localization (3,7). Finally, STXYL2/ DUSP27 is believed to be a putative pseudophosphatase containing a conserved phosphatase catalytic domain like other dual-specificity phosphatases but lacking the highly conserved cysteine residue found at the base of the catalytic loop in active phosphatases of the DUSP family (Fig.…”
mentioning
confidence: 99%
“…Both genes are expressed in skeletal muscle and few other tissues (4,5,7). Furthermore, the protein product of both genes localizes predominantly to the cytoplasm of cells and tissues that have been studied, and both proteins have been shown to play a role in cell-signaling pathways important for cell growth and development (2)(3)(4)7). Finally, each protein possesses a putative phosphatase domain, although only DUPD1/DUSP27 encodes a protein that has been shown to be catalytically active (Fig.…”
mentioning
confidence: 99%